PERAN BRAND LOVE MEMEDIASI PENGARUH BRAND SATISFACTION TERHADAP BRAND LOYALTY (Studi pada pelanggan Toko Buku Gramedia di Kota Denpasar) - Putu Laksmita Dewi Rahmayanti; Ni Nyoman Kerti Yasa; I Gusti Ayu Tirtayani (Warmadewa Management and Business Journal (WMBJ), 2024)
The purpose of this study was to test and explain the role of brand love in mediating the effect of brand satisfaction on brand loyalty. The population of this study were people in Denpasar City who had shopped for books at least 2 times at Gramedia Bookstore in the past year. The sample size used was 110 people with purposive sampling method. The analysis technique used is Path Analysis using SEM-PLS. The results showed that brand satisfaction has no effect on brand loyalty, brand satisfaction has a positive and significant effect on brand love, and brand love has a positive and significant effect on brand loyalty, and brand love is able to fully mediate the effect of brand satisfaction on brand loyalty. This means that brand love is very important to exist between the influence of brand satisfaction on brand loyalty so that its influence becomes significant. Therefore, in the future, Gramedia bookstore really needs to build brand love from its customers.